2006
DOI: 10.1210/jc.2005-2698
|View full text |Cite
|
Sign up to set email alerts
|

Relation between Circulating Angiotensin II Type 1 Receptor Agonistic Autoantibodies and Soluble fms-Like Tyrosine Kinase 1 in the Pathogenesis of Preeclampsia

Abstract: We conclude that AT1-AA bioactivity and sFlt1 concentrations do not correlate, are not mutually dependent, and are thus probably involved in distinct pathogenetic mechanisms. Both factors in combination may not be causative for the early impaired trophoblast invasion and pathological uterine perfusion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
34
1
2

Year Published

2007
2007
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(41 citation statements)
references
References 15 publications
4
34
1
2
Order By: Relevance
“…Furthermore, the renin-angiotensin system, either through angiotensin II or angiotensin II receptor type 1-auto antibody, may also be a contributing factor, although this appears to be more contentious based on recent findings in the human literature. 32 Alternatively, the present work suggests that VEGF supplementation may hold potential as a possible intervention in preeclamptic pregnancies. Lastly, we feel that the present work provides a platform from which other studies may be launched to elucidate underlying mechanisms and to develop efficacious interventions for preeclampsia.…”
Section: Perspectivesmentioning
confidence: 76%
“…Furthermore, the renin-angiotensin system, either through angiotensin II or angiotensin II receptor type 1-auto antibody, may also be a contributing factor, although this appears to be more contentious based on recent findings in the human literature. 32 Alternatively, the present work suggests that VEGF supplementation may hold potential as a possible intervention in preeclamptic pregnancies. Lastly, we feel that the present work provides a platform from which other studies may be launched to elucidate underlying mechanisms and to develop efficacious interventions for preeclampsia.…”
Section: Perspectivesmentioning
confidence: 76%
“…[73][74][75][76][77][78][79][80] Recently, studies have reported that increased sFlt-1 may have a predictive value in diagnosing preeclampsia as concentrations seem to increase before manifestation of overt symptoms (eg, hypertension, proteinuria). 73,[81][82][83][84] In an elegantly designed study reported several years ago, Maynard et al 85 reported that exogenous administration of sFlt-1 into pregnant rats via adenovirus mediated gene transfer resulted in increased arterial pressure and proteinuria, and decreased plasma free VEGF and PlGF concentrations similar to that observed in the preeclamptic patients. Subsequently, similar observations using adenovirus transfection have been reported in the mouse.…”
Section: Angiogenic Factorsmentioning
confidence: 90%
“…Furthermore, AT1-AA stimulates sFlt-1 and sEng by inducing TNF-a and overcoming its negative regulator, HO (59). In terms of human studies, Stepan et al (60) did not find a correlation between AT1-AA and sFlt-1 levels, whereas Siddiqui et al (61) did. Given these mixed results in humans, it remains questionable whether AT1-AA and sFlt-1 levels share the same pathophysiologic mechanism.…”
Section: Angiotensin Receptor 1 Autoantibodiesmentioning
confidence: 98%